2019
DOI: 10.1002/ldr.3346
|View full text |Cite
|
Sign up to set email alerts
|

Isobaric tags for relative and absolute quantification‐based proteomic analysis of Puccinellia tenuiflora inoculated with arbuscular mycorrhizal fungi reveal stress response mechanisms in alkali‐degraded soil

Abstract: Alkali soil is a major abiotic constraint that limits plant distribution and yield in the northeast of China. Puccinellia tenuiflora is considered the most promising grass species for salt‐alkali grassland restoration. However, there is little information on the molecular mechanisms underlying how arbuscular mycorrhizal fungi (AMF) enhances P. tenuiflora stress responses in alkali‐degraded soil. In this study, AMF colonization, growth, photosynthetic pigments, and inorganic ion contents were measured. Isobaric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 65 publications
0
10
1
Order By: Relevance
“…Hence, understanding the positive effect of AMF on this species is crucial for its use in grassland rehabilitation and restoration. Our previous studies showed a good symbiotic relationship between AMF and this species under salt and alkali stresses ( Lin et al, 2017 ; Wang et al, 2019a ; Wang et al, 2019b Wang et al, 2019c ; Yang et al, 2020a ; Yang et al, 2020b ). In the present study, we hypothesized (1) that AMF play an important role in alleviating the inhibitory effect on seedling growth under alkali or drought stress conditions and (2) that the interaction of alkali and drought stresses affects the alleviating effect of AMF in Leymus chinensis seedlings.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Hence, understanding the positive effect of AMF on this species is crucial for its use in grassland rehabilitation and restoration. Our previous studies showed a good symbiotic relationship between AMF and this species under salt and alkali stresses ( Lin et al, 2017 ; Wang et al, 2019a ; Wang et al, 2019b Wang et al, 2019c ; Yang et al, 2020a ; Yang et al, 2020b ). In the present study, we hypothesized (1) that AMF play an important role in alleviating the inhibitory effect on seedling growth under alkali or drought stress conditions and (2) that the interaction of alkali and drought stresses affects the alleviating effect of AMF in Leymus chinensis seedlings.…”
Section: Introductionmentioning
confidence: 85%
“…Thiobarbituric acid (0.6%. one mL) was used to extract malondialdehyde (MDA) from fresh shoots (200 mg), and the absorbance was then measured at 600, 532 and 450 nm ( Wang et al, 2019a ; Wang et al, 2019b Wang et al, 2019c ). Proline was extracted with 3% sulfosalicylic acid for 1 h, and the absorbance was measured at 520 nm ( Bates, Waldren & Teare, 1973 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NaHCO 3 ) and salt-tolerance plant E. angustifolia under salt stress (300 mM NaCl) (Jia et al, 2019;Wang et al, 2019). The inconsistency may imply that the regulation of AMF on these pathways in halophytes differs with the environment, that is, between under the moderate and high salinity stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, proteomics technologies have been employed to identify the proteins inducted by AMF, and reveal the mechanisms of AM symbiosis tolerating abiotic stresses at the protein level (Bai et al, 2019;Wu et al, 2019). For instance, the AMF Rhizophagus intraradices can significantly improve protein synthesis, nitrogen metabolism and ROS scavenging to boost osmotic substance biosynthesis and response to alkaline stress in a salt-alkali grass Puccinellia tenuiflora by proteomics (Wang et al, 2019) S. salsa is widely distributed in Asia, and grows in littoral and inland salt soils in China, and the species is a leaf-succulent halophytic herb that is able to accumulate salts in shoots and can be used to restore salty soils (Song & Wang, 2015). Its favorable salt concentration is from 100 to 300 mM NaCl for vigorous growth (Qiu et al, 2007).…”
mentioning
confidence: 99%